Lift Off Process on Fabrication of Carbon Monoxide (CO) Gas Sensor Devices - Slamet Widodo; Goib Wiranto (UNIVERSITAS SEBELAS MARET (UNS), 2014)
This paper discuss the design and fabrication of microdevice to be used as platform for CO (Carbon monoxide) gas sensor based on tin dioxide (SnO2). The device has been designed on silicon substrate with an active area of 3x3 mm2, and it is consist of bonding pad, heater, electrode, and temperature sensor components. The minimum feature size used is 50 microns, as allowed by the capability of photolithographic process. The formation of microdevice structure was carried out by lift-off technique on platinum (Pt) layer, which was deposited by DC sputtering with aluminum (Al) as sacrificial layer. The overall chip dimension is 5x5 mm2. The measurement that was conducted to study the characteristic of resistance asfunction of temperature has shown that the heater and temperature sensor elements could work as expected, in which their resistances change linearly as the temperature of the substrate increase by 20–200 °C. The resistance values of the heater increase 500–1000 ohm. Meanwhile, the resistance increasing for temperatur sensor is between 100–300 ohm.